Evaluation Of The Implementation Of Primary Care (P-Care) Application At Puskesmas Onolalu Nias Selatan In 2022 - Ohito Laia; Sri Lestari Nasution; Johanes Ginting (International Journal of Health and Pharmaceutical (IJHP), 2023)
Primary Care (P-Care) is a patient information service using the internet and computer-based provided by BPJS Health for primary health facilities to provide easy access to data to the BPJS server for both registration and medical services. The purpose of this study was to evaluate the implementation of the Primary Care (P-Care) application at the Onolalu Health Center UPTD South Nias Regency in 2022. This research is qualitative research with a phenomenological approach. The informants in this study were all officers holding the P-Care application, totaling 5 officers. The data analysis method used in this research is descriptive qualitative with the stages of data reduction, data display, and conclusion or verification. The results of the study show that the production implementation of the p-care application makes all processes from registration to the referral process easier, the efficiency implementation of the p-care application makes all patient handling to get health services much easier and saves time and the implementation of the satisfaction of the p-care application making officers, patients and the puskesmas itself very satisfied. Based on the research results, it is hoped that the puskesmas will always improve the quality of services related to the use of p-care applications such as strengthening the internet network, so that each patient visit data can be input on time, as well as increasing the workforce of graduates from D-III Medical Records so that the application of primary care ( p-care) to be more optimal.